Pemberdayaan Kemampuan Berpikir Kreatif Berbasis Literasi pada Anak Panti Asuhan Aisyah Bekonang Mojolaban Sukoharjo - Ima Aryani; Dian Putri Utami; Azzahra Amay Ririh (Universitas Sebelas Maret, 2025)
Literacy skills are basic skills that students must have, including children from the Aisyah Bekonang Orphanage (PAKEM). Children in orphanages must receive proper education at the secondary school level (SMP and SMA). According to the results of observations, children in orphanages do not have mobile phones (HP), there are not enough facilities to access the digital world. This community service aims to: (1) Provide an understanding to children in orphanages about literacy, (2) empower students' literacy skills based on media in the surrounding environment, (3) empower creative thinking skills based on literacy. The target of this activity is 25 children in orphanages consisting of junior high school (SMP) and high school (SMA) levels. The method implemented in this community service is the preparation stage which includes observation activities, determining the schedule and the preparation stage for the necessary tools and materials. The second stage is the implementation stage which includes delivering material on literacy and is continued with literacy activity training. The results of this activity are (1) increased understanding of literacy in orphanage children, (2) literacy skills in orphanage children begin to develop, (3) creative thinking skills in orphanage children develop as expected.